1972
DOI: 10.7589/0090-3558-8.1.85
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Climate on the Seasonal Prevalence of Plague in the Republic of Vietnam

Abstract: An 8 year study of the influence of climate on the seasonal prevalence of bubonic plague in the Republic of Vietnam has been completed. Climatic conditions were found to influence the course of plague epidemics in 2 ways: 1) by regulating the density of the flea population; and, 2) by regulating the efficiency of Xenopsy/la ebieopis in transmitting the plague bacillus. Slight variations in temperature, relative humidity, and vapor pressure deficits either permit an epidemic to flourish or cause a decline in it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 0 publications
2
69
0
1
Order By: Relevance
“…This correspondence provides support for a (temperature-modulated) trophic cascade model for plague (22). In contrast to the studies from North America, however, in Vietnam most human plague cases have been found to occur in dry seasons (23); the risk of plague increased during dry seasons when rainfall was <10 mm (24), showing that the trophic cascade hypothesis may not be generally valid.…”
mentioning
confidence: 46%
See 1 more Smart Citation
“…This correspondence provides support for a (temperature-modulated) trophic cascade model for plague (22). In contrast to the studies from North America, however, in Vietnam most human plague cases have been found to occur in dry seasons (23); the risk of plague increased during dry seasons when rainfall was <10 mm (24), showing that the trophic cascade hypothesis may not be generally valid.…”
mentioning
confidence: 46%
“…Experimental work has shown that relative humidity significantly affects the survival of fleas (40). Climate conditions were found to influence human plague cases in Vietnam by regulating the density of the flea population and by regulating the efficiency of X. cheopis in transmitting the plague bacterium (23).…”
Section: Discussionmentioning
confidence: 99%
“…Proventricular colonization and blockage was hypothesized to result from bacteria-laden clots lodging among the proventricular spines. This hypothesis was compelling because it could also explain the decrease in proventricular blockage and flea-borne transmission during hot weather (Cavanaugh and Marshall 1972). The fibrin-dissolving activity of Pla that predominates at higher temperatures was invoked to explain that phenomenon.…”
Section: The Coagulase Model Of Proventricular Infectionmentioning
confidence: 94%
“…In addition, the positive association with wetness, as expressed by the inclusion of band 6, may be indicative of conditions that are conducive to flea survival. In general, fleas are susceptible to desiccation-induced mortality, 41 particularly when temperatures are fairly high as they would be during the month of January when the Landsat images were captured. Vectorial capacity models suggest that as flea survivorship increases, the probability of flea-borne transmission also increases.…”
Section: Discussionmentioning
confidence: 99%